Clinging to bars or capsizing barriers? a study on the TV programme Captain Barbell : ang Pagbabalik and the portrayal of men and masculinity - Sayno, Ericson Carlo Alquisola 1992- (2012)
"This study presents how men and masculinity are represented in television through the characters Teng and Captain Barbell in the TV program Captain Barbell: Ang Pagbabalik. Mass media is the biggest venue for gender stereotyping. Men have been stereotyped as dominant figures in society as well as in media such as TV shows and advertisements. Television is thought of as a purveyor of gender stereotypes, that watching TV reinforces belief in them (Zemach & Cohen, 1986). The Blueprint for Manhood Model and Queer Theory provide theoretical basis for this study. The researcher employed textual analysis to find out the indicators necessary to answer the research objectives and created a textual analysis matrix to record his observations based on the roles Teng and Captain Barbell played and the behavior they exhibited in the course of the story. Through the study, the researcher found out that Captain Barbell: Ang Pagbabaik features two contrasting images of men and masculinity. Captain Barbell epitomizes the dominant and aggressive man while Teng is the docile and emotional man. Teng's deviation from the stereotypical man is proof that not all content shown on television cling to the gender stereotypes constructed by society."